Processes of spatial appropriation and social inequalities in the Historic Center of Puebla - Alvarez Moura, Alfonso; Valverde Díaz de León, Francisco (Geografares, 2017)
Linking forms of intervention in the city and processes of socio- spatial appropriation in the historic center of Puebla. We discuss specific caseloads of dispossession - appropriating space that delve into social inequalities. With all this, we intend to verify the relationship between the use made of the Historical Center and social appropriation class that is the subject. Keywords: Historic Centers, Heritage Urban, Urban Renewal.